2015
DOI: 10.2527/jas.2014-8723
|View full text |Cite
|
Sign up to set email alerts
|

Feedlot performance and carcass traits of hairbreed ewe lambs in response to zilpaterol hydrochloride and soybean oil supplementation

Abstract: The aim of the present study was to evaluate the impact of zilpaterol hydrochloride (ZH; 0 or 10 mg/lamb daily) and soybean oil (SBO; 0 or 6%) supplementation on feedlot performance, carcass traits, and wholesale cut yield of 32 Dorper × Pelibuey ewe lambs (30.55 ± 2. 57 kg of initial BW). Lambs were blocked by BW and randomly assigned to treatments under a randomized complete block design with a 2 × 2 factorial arrangement. After a 34-d feeding period, all ewes were slaughtered. No ZH × SBO interactions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…Thus, ZH in lambs increases the formation of lean meat and, hence, the carcass weight and yield, as well as LM area at the same time that internal fat deposition decreases. Consistent with the present study, most studies in sheep have reported a lack of ZH effects on energy repartition away from subcutaneous fat (Estrada-Angulo et al 2008;Macias-Cruz et al 2010;Ríos-Rincón et al 2010;Dávila-Ramírez et al 2014, 2015.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, ZH in lambs increases the formation of lean meat and, hence, the carcass weight and yield, as well as LM area at the same time that internal fat deposition decreases. Consistent with the present study, most studies in sheep have reported a lack of ZH effects on energy repartition away from subcutaneous fat (Estrada-Angulo et al 2008;Macias-Cruz et al 2010;Ríos-Rincón et al 2010;Dávila-Ramírez et al 2014, 2015.…”
Section: Discussionsupporting
confidence: 90%
“…slaughter has shown to consistently improve growth and feed efficiency in beef cattle (Avendaño-Reyes et al 2006;Lean et al 2014); however, it has been inconsistent in finishing lambs. Some studies have reported no effects (Macias-Cruz et al 2010;Dávila-Ramírez et al 2015), improvements of growth rate and feed efficiency without affecting DMI (Estrada-Angulo et al 2008;Mondragón et al 2010;Avendaño-Reyes et al 2011) or increased growth rate, and feed efficiency and decreased DMI (López-Carlos et al 2011, 2012 in sheep after 30-34 d consuming feedlot diets supplemented with ZH. Improvement in growth rate has been the most consistent and DMI the least consistent effect of ZH on sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Avendaño et al [1] reported that wholesale cuts were not affected by ZH, except for neck yield, which decreased (based on HCW) with feeding ZH. The percentage of loin is greater in ewe lambs fed ZH [33]. The variation in response to ZH supplementation among wholesale cut yields obtained from lamb carcasses could depend on the presence and amount of type II muscle fibers located in each cut, given that β2-adrenergic receptors are mainly located in these fibers [34].…”
Section: Discussionmentioning
confidence: 99%
“…En ovinos de pelo finalizados con diferentes dosis de CZ genérico en dos experimentos (22) , se reportó un aumento cuadrático en el largo de canal, profundidad de tórax y perímetro de pierna como la dosis ofrecida de CZ aumentó de 0 a 0.20 mg/kg de peso vivo. En corderos (24,28) y corderas (19) también han encontrado un aumento en el perímetro de pierna sin efecto alguno en otras medidas morfométricas a consecuencia del CZ de patente.…”
Section: Discussionunclassified
“…En el caso del grupo testigo, a manera de placebo, una cápsula de gel que contenía 208 mg de harina de soya fue ofrecida diariamente a cada cordero. La dosis ofrecida de CZ estuvo acorde a recomendaciones de estudios previos (18,19) . EL CZ se ofreció por 28 días, seguido de un periodo de retiro de 48 h antes de sacrificar los animales.…”
Section: Tratamientos Y Alimentación Experimentalunclassified